Binarization of First Temple Period Inscriptions: Performance of Existing Algorithms and a New Registration Based Scheme - Shaus, A.; Turkel, E.; Piasetzky, E. (2012 International Conference on Frontiers in Handwriting Recognition, 2012)
The discipline of First Temple Period epigraphy (the study of writing) relies heavily on manually-drawn facsimiles (black and white images) of ancient inscriptions. This practice may unintentionally mix up documentation and interpretation. As an alternative, this article surveys the performance of several existing binarization techniques. The quality of their results is found to be inadequate for our purpose. A new method for automatically creating a facsimile is then suggested. The technique is based on a connected-component oriented elastic registration of an already existing imperfect facsimile to the inscription image. Some empirical results, supporting the methodology, are presented. The procedure is also relevant to the creation of facsimiles for other types of inscriptions.